Efektivitas Media Tangram Berpetak Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Voni Susilastuti; Neda Permana (Journal on Education, 2021)
This study aims to determine the effect of square-grid tangram media on student learning result, especially on polygon material. This research is a quasi-experimental study with the design of one group pre-test post-test conducted at one of the Elementary Schools in Bandung Regency. The samples from this study were 32 students with learning using square-grid tangram media. The data was processed with the help of IBM SPSS version 26. The test steps are 1) The Normality Test, and 2) T-Test. The conclusions of this study are 1) Achieving the ability of students in many facets using tangram media better, 2) The use of tangram media is more effective when used in polygon material, 3) Students more quickly understand the material and students feel motivated.